Morphological phylogenetic analysis of Ophrys (Orchidaceae): insights from morpho‐anatomical floral traits into the interspecific relationships in an unresolved clade. (17th September 2015) - Francisco, Ana; Porto, Miguel; Ascensão, Lia
<x xml:space="preserve">Abstract</x> Reconstructing the phylogeny of the sexually deceptive orchid genus Ophrys is crucial to our understanding of the evolution of its complex floral morphology. Molecular phylogenetic analyses showed that section Pseudophrys forms a well supported clade with Ophrys bombyliflora, O. tenthredinifera and O. speculum, but were unable to elucidate the relationships between these four groups of taxa. Here we conduct a morphological phylogenetic analysis of this unresolved clade of Ophrys based on a data matrix of 45 macro‐ and micromorphological and anatomical floral characters, using maximum parsimony and Bayesian inference. Our cladistic analysis yielded a single most parsimonious tree and a Bayesian 50% majority‐rule consensus tree which differed in their overall topology but agreed that O. tenthredinifera and O. bombyliflora are not sister groups. The phylogenetic placement of O. tenthredinifera was ambiguous since it shares six valid synapomorphies each with the cluster of O. speculum–O. bombyliflora and with section Pseudophrys. In contrast, O. bombyliflora is most likely the sister group to O. speculum, a finding that rejects an earlier morphological phylogenetic hypothesis and favours the existing molecular trees based on nuclear ITS rather than plastid data. © 2015 The Linnean Society of London, Botanical Journal of the Linnean Society, 2015, 179, 454–476.